Thermal response of Bragg gratings in PMMA microstructured optical fibers - Carroll, Karen E.; Zhang, Chi; Webb, David J.; Kalli, Kyriacos; Argyros, Alexander; Large, Maryanne C J (My University, 2007)
We report on the thermal characteristics of Bragg gratings fabricated in polymer optical fibers. We have observed a permanent shift in the grating wavelength at room temperature which occurs when the grating has been heated above a threshold temperature. This threshold temperature is dependent on the thermal history of the grating, and we attribute the effect to a shrinking of the fiber. This effect can be avoided by annealing the fiber before grating inscription, resulting in a linear response with temperature and an increased linear operating temperature range of the grating.
Keywords: Optical fibers; Bragg gratings; Microstructure